Fluidized bed chemical vapor deposition synthesis of carbon nanotubes and its application for cellulase immobilization - Danafar, Firoozeh (2010)
Over the past decade, Carbon Nanotubes (CNTs) have evolved into one of the most important material under investigation, as they can be used in various applications, due to their excellent unique characteristics. If the CNTs are ever to fulfill their promise as an engineering material, commercial production will be required. Recent advances on Chemical Vapor Deposition (CVD) synthesis of CNTs have shown that fluidized bed reactors have a great potential for commercial production of this valuable material. However, Fluidized Bed Chemical Vapor Deposition (FBCVD) is still in its infancy and further studies and innovations are needed. Accordingly, the first objective of this study was to develop a FBCVD process for the synthesis of CNT using ethanol (as a carbon source) in the presence of iron and cobalt catalysts supported on alumina. At this stage, attempts were made to find the best value for ethanol flow rate and amount of catalytic particles. The second objective was to investigate the inherent characteristics of catalytic particles, namely, composition and particle size range on FBCVD synthesis of CNT. The maximum carbon deposition efficiency obtained from the experiments was 85%. The deposited carbon was estimated to contain CNTs with a purity of approximately 98% based on thermogravimetric analysis. This result was achieved when 5 g catalytic particles comprising iron: cobalt, with weight percentage of 2:1% and particles size of 10-20 μm were fed into the reactor and the operating parameters including ethanol flow rate, temperature and time of the reaction were set at 2 Sccm, 600 ºC and 30 min, respectively. In addition to the FBCVD synthesis of CNTs, the possibility of cellulase immobilization on carriers consist of CNT was investigated. A circular-shaped flake nanocomposite made of chitosan-CNTs with a uniform diameter of about 4 mm was fabricated and examined for cellulase immobilization. Physical adsorption of cellulase on carriers composed of chitosan-CNTs revealed that the activity of the immobilized cellulase on the chitosan-CNTs supports is about 3.25 U/g, which is fairly higher than the activity of the immobilized enzyme on the pure chitosan carriers (~ 2 U/g). The activity of the immobilized cellulase on chitosan-CNT carriers was estimated approximately 65% of the free cellulase activity (5.4 U/g), while it was only 40% for enzyme immobilized on pure chitosan supports. Moreover, the immobilized cellulase on the chitosan-CNTs carriers had almost 70% of the fresh enzyme activity after using it three times. They also retained about 85% of the initial activity after two weeks storage at 4 ºC. In this dissertation, a selective FBCVD process for gram scale production of CNT was developed. Besides that, it was shown that the characteristics of the catalytic particles, composition and particle size range, have significant impacts not only on the process efficiency but also on the product selectivity and its morphology. In further attempts, the feasibility of using CNT for cellulase immobilization was investigated. Results indicated significant improvement on the physical adsorption of cellulase when the carriers composed of CNT was used. The enzyme reusability and storage ability were also improved when CNT was present in the carriers.